Application of Science and Technology for Rice Farmers Facing Pest Golden Snails in The Village of Bunut Baok, Central Lombok - Suripto; Gunawan E.R; Aryanti, E; Sukiman (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The golden snail in Indonesia is a species of foreign animal, originally kept as a decorative animal in an aquarium but later turned into a pest of plants, especially rice plants. This golden snail attack can cause rice crop production to decrease by up to 30%. The use of synthetic pesticides to control golden snails is not recommended because they must use very high concentrations, which endanger the lives of non-target organisms. Synthetic chemical pesticides are generally stable and not easily degraded so that they accumulate in the food chain. A number of studies have been conducted to find the effective use of botanical pesticides to control the golden snail, a pest of rice plants. Natural pesticides from the jayanti plant (Sesbania sesban) have been laboratory-proven to be effective and selective for the control of golden snails, namely killing golden snails as pests but not killing non-target animals. The manufacture and application of molluscicides from jayanti plants can be easily carried out by farmers, because the active anti-mollusc content can be withdrawn using water as the sole solvent. Devotion activities on the application of science and technology for rice farmers who face the golden snail problem have been carried out in Bunut Baok Village, Central Lombok. This activity began with a coordination meeting of the implementation team with the village head and farmer group leaders in Bunut Baok Village to confirm the problems faced by rice farmers, determine methods and implementation schedule. This service activity aims to increase the appreciation of the farming community for the jayanti plant, increase the knowledge and skills of farmers in producing molluscicides from jayanti plants and apply them to control golden snails in rice fields. Socialization of the application of science and technology was carried out using various methods and media, including lectures, simulations, demonstrations, discussions, field practices and mentoring. The activity was attended by 12 members of Mohon Petunjuk Farmers Group in Bunut Baok Village. The results achieved from this activity are increasing farmers' appreciation for jayanti plants and increasing farmers' knowledge and skills in producing natural molluscicides from jayanti plants and applying them to control the golden snail pest of rice plants.